Two Phenotype-Differentiated Acinetobacter baumannii Mutants That Survived in a Meropenem Selection Display Large Differences in Their Transcription Profiles - Gao, Qianqian; Meng, Xiaobin; Gu, Hanfu; Chen, Xueqin; Yang, Huaqing; Qiao, Yangyang; Guo, Xuemin (Frontiers in Microbiology, 2019)
37662RM1 and 37662RM2 are two phenotypically different, carbapenem-resistant mutants of Acinetobacter baumannii 37662 isolated following selection with meropenem at sub-inhibitory concentrations. 37662RM2 lacks capsule synthesis and shows dramatically increased biofilm formation, while 37662RM1 shows merely impaired capsule synthesis. Here we report that 37662RM1 and RM2 have transcription profiles that are different from those of their starting strain, 37662WT. There were far more differentially expressed genes in 37662RM2 than in 37662RM1. The capsule polysaccharide (CPS) synthesis-required genes (itrA2, gtr5, psaA, psaB, psaC, psaD, psaE, psaF, kpsS2, wzx, wzy, wza, wzb, and wzc) showed reduced transcription levels in 37662RM2, which may at least partially explain the loss of capsule synthesis. The csu operon genes responsible for pili assembly and their regulator genes bfmR-bfmS were over-expressed in 37662RM2. This result together with the established critical roles of these genes in biofilm formation provide solid evidence that up-regulation of csu and bfmR-bfmS should be considered responsible for the enhanced biofilm formation in 37662RM2. ISAba1 was found to insert into the intergenic region between the csu operon and the acrR gene and should be responsible for the significant up-regulation of acrR, which was proposed to be associated with biofilm formation. Genome sequencing revealed that the ISAba1 upstream blaOXA-508 (a new member of blaOXA-51-like) and acrR were duplicated, suggesting a replicative transposition event. Altogether, the phenotype divergence driven by meropenem selection mainly occurs at the RNA level and the transposition of ISAba1 plays an important role in modulating gene expression to adapt to the environment.